A study of Atlantic salmon (Salmo salar L.) smolt behaviour at the Pointis hydroelectric powerhouse water intake on the Garonne river and an estimate of downstream migration over the Rodere dam - Croze, O.; Larinier, M. (HAL CCSD, 1999)
National audience An experiment was conducted in 1998 at the Pointis water intake, on the Garonne river, to define location for a future downstream bypass for Atlantic salmon smolts. The study of the movements of 28 radio tagged smolts revealed that under low hydraulic conditions (flow velocities < 0.5-0.6 m/s), the smolts maintain their position for a significant time (median time greater than one day) in the intake canal, despite the large spacing (5 cm) between the bars of the trashrack. During this time, they explore the whole area of the intake canal above the trashrack. A light placed on the left bank just upstream from the trashrack concentrated the fish on the same bank as the lamp, in the vicinity of the lighted area. The proportion of fish passing downstream from the Rodere dam itself, located downstream from the Pointis plant, was estimated. It appeared that the proportions of smolts passing through the Rodere dam were related to the ratio of discharge at the dam to the total Garonne flow : 70% of the smolts passed by when the discharge at the dam corresponded to 40-50% of the total Garonne flow. The time taken by radio tagged smolts to go from the Pointis plant to the Camon powerhouse varied from 1h 17 min to 12 days with a median value of more than one day, and depended on river discharges. The downstream displacements in the intake canals of Pointis (1.9 to 4.2 km/h) and Camon (2.5 to 7 km/h) were positively correlated with flow velocities. Une expérimentation a été menée en 1998 au niveau de la prise d'eau de l'usine hydroélectrique de Pointis, sur la Garonne, de manière à déterminer, grâce à la technique de radiopistage, le meilleur emplacement d'un futur dispositif de dévalaison. Le suivi des déplacements de 28 smolts radiomarqués a mis en évidence que, dans des conditions hydrauliques peu marquées (vitesses de courant < 0.5-0.6 m/s), les poissons peuvent stationner des temps conséquents (valeur médiane supérieure à 1 jour) en amont immédiat de l'usine et ce, malgré un espacement de 5 ...